Holocene Ostracoda (Crustacea) from the shallow Lake Vrana (Dalmatia, Croatia) and their paleoenvironmental significance - Hajek-Tadesse, Valentina; Ilijanić, Nikolina; Miko, Slobodan; Hasan, Ozren (Quaternary international, 2018)
Lake Vrana in Dalmatia is a coastal karstic brackish water environment characterized by a high species richness of ostracods that evolved into their current morphologies during the Holocene. The results of this study reveal five ostracod zones within an 11 m sediment core taken from the central part of the lake. This sedimentary sequence reveals significant changes in both depositional and environmental conditions at local and regional scales; the oldest freshwater deposits, interpreted as the Late Pleistocene/Holocene transition, mainly comprise the species Candona neglecta, Juxilyocypris cf. schwarzbachi, Hungarocypris madaraszi, Darwinula stevensoni, and Mixtacandona sp. Although the lake had not formed at this time, it is well known that the living environment of most ostracod species is connected to flooded plains, marshes, rivers, springs, and interstitial waters. In the deepest and oldest sediments within the core, from depths between 1101 cm and 945 cm, the presence of C. neglecta and J. cf. schwarzbachi are indicative of cold water, while the dominant taxa at depths between 945 cm and 874 cm are the brackish species Cyprideis torosa and C. angulata, possibly suggesting the influence of seawater because of the presence of a permeable karstic ridge that separates the lake from the ocean. In contrast, the dominant ostracod taxa at depths between 874 cm and 813 cm are species typical of freshwater environments subject to colder climatic conditions indicating a marshy, low-energy wetland. We know that the first permanent freshwater body formed at about 8130 cal yr BP (a depth of 813 cm), while large proportions of Pseudocandona marchica, Heterocypris salina, D. stevensoni, and Metacypris cordata are all indicative of warmer, shallow waters that are rich in vegetation and have variable water level. Similarly, from 5240 cal yr BP onwards, a marine influence within the core is evidenced by the presence of Cy. torosa, while present lake water conditions (i.e., alternating seasonal changes in salinity from freshwater to brackish) were established by 2750 cal yr BP. The ostracod assemblages in sediments from Lake Vrana in Dalmatia have significant potential for reconstructing the evolution of this lake as well as for understanding environmental changes and rising sea level.